TEACHING SPEAKING AND WRITING AT JUNIOR AND SENIOR HIGH SCHOOLS AS DEMANDED BY CURRICULUM 2013 - Jufri, Jufri (English Department FBS UNP, 2016)
Speaking and writing are two productive language skills that should be taught by English teachers at junior and senior high schools in Indonesia as demanded by Curriculum 2013. Based on the current syllabus, known as Kurikulum 2013, the teaching of speaking and writing at junior and senior high schools is based on genre or kinds of texts. In this case, the students are provided with competences as stated in Core Competence (Kompetensi Initi) and Basic Competence (Kompetensi Dasar) of the syllabus. The objectives of speaking and writing classes are to enable the students to communicate based on the needed texts, such as transactional/interpersonal, functional and monologue texts. To gain this, a teacher should design a teaching model by selecting and using appropriate technique and teaching activities. The technique chosen will determine the teacher’s success and the students’ achievement in the class. The technique, however, is not sufficient to achieve the teaching objectives if the teacher does not prepare appropriate activities for the students. The teaching and learning activities will help the students to gain the needed competences as demanded by Kompetensi Dasar (basic competence) in the syllabus. For this purpose, in this paper the writer discusses about speaking and writing activities that can be implemented in the classroom. Key words: Competence, Curriculum 2013, Genre, Activities